2018
DOI: 10.1166/jnn.2018.15532
|View full text |Cite
|
Sign up to set email alerts
|

Thermoluminescence from Cu Doped Lithium Tetraborate Irradiated with X-ray and γ Using 137Cs Radioactive Source

Abstract: Lithium tetraborate (Li2B4O7) pellets prepared by using water/solution assisted method were synthesized and characterized. Copper was used as doping material in order to enhance the Li2B4O7 thermoluminescent properties. For synthesis heating temperature parameters were defined at 750 °C for 2 hr, followed by 150 °C for another 2 hr. The materials were produced at five different Cu concentrations: 0.02, 0.04, 0.06, 0.08, and 0.1 wt%. The luminescent and morphological characterizations were performed by X-ray di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…To choose a suitable activator for LiB 3 O 5 , the synthesised sample was doped with different concentrations (0.1, 0.2, 0.3, 0.4, 0.5, 1, 2, 3, and 4 wt %) of various dopants such as Al, Cu, Mn, Mg and PVP. These dopants were selected based on the previous studies on lithium tetraborate [6][7][8][9][10][11][12] and lithium triborate [14][15][16][17][18]. The doped nanophosphors were sintered at 710°C for 4 h and their response to irradiation was investigated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To choose a suitable activator for LiB 3 O 5 , the synthesised sample was doped with different concentrations (0.1, 0.2, 0.3, 0.4, 0.5, 1, 2, 3, and 4 wt %) of various dopants such as Al, Cu, Mn, Mg and PVP. These dopants were selected based on the previous studies on lithium tetraborate [6][7][8][9][10][11][12] and lithium triborate [14][15][16][17][18]. The doped nanophosphors were sintered at 710°C for 4 h and their response to irradiation was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, lithium borates with an effective atomic number similar to the biological tissue are appropriate materials for radiation dosimetry purposes [4,5]. Most of the studies on TL properties of lithium borates are performed on lithium tetraborate (bulk or nanosized) with various activators [6][7][8][9][10][11][12]. These studies have shown that TL properties of lithium tetraborate depend on the synthesis method, type, and concentration of dopants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation